Bentuk, Makna, dan Fungsi Register Pemain Game Online Dragon Raja:SEA - Mulyono Mulyono (Lingua Susastra, 2022)
In this study, the register of players for the online game Dragon Raja:SEA is discussed. Due to the uniqueness of the language used in the speech group, this research is needed to understand the specific language they use which can only be understood by members of the speech group. The purpose of this study was to analyze the form, meaning, and function of registers in the game Dragon Raja: SEA. The purpose of this study was to analyze the form, meaning, and function of registers in the game Dragon Raja: SEA. The approach used is a qualitative approach. The data was collected using the conversational engagement listening technique and the advanced technique using note-taking and recording techniques. The data source of this research is the online game player Dragon Raja: SEA. The data source of this research is the online game player Dragon Raja: SEA. The data required is in the form of sentences containing registers. The data analysis method used is descriptive qualitative method with stages 1) collecting data, 2) transcribing oral data into written data, 3) analyzing data according to register theory, and 4) concluding the data obtained. The results found are 1) forms that are divided into words, phrases, abbreviations; 2) meaning; and 3) functions, which consist of a) summarizing orders, b) facilitating communication, c) establishing intimacy, d) giving insults, and e) giving praise.